Analysis about production of nursing knowledge on health education and aging: review article - Isis Marques Severo; Maria Cristina Sant'Anna da Silva; Maria Isabel Pinto Coelho Gorini (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This study is exploratory, of qualitative nature and has the objective to identify the bibliographical production of nursing related to the aging, to the education in health and the methodological strategies, in Brazilian publications, from 2000 to 2006. Online database BDENF was used to search the articles and the keywords were: health education, aged, aging, behavior and nursing. Eight articles had been identified and five were chosen which are in the following publications: Revista Brasileira de Enfermagem (two), Revista Latino-Americana de Enfermagem (two) and Cogitare Enfermagem (one). The discussion of the selected articles was based on the technique of content analysis. The results had demonstrated that the subjects education in health and aged people have little space in researches by Brazilian nursing, in this period and at the database consulted, and group activity was distinguished as predominant methodological strategy of education in health. In such activity, the promotional actions of the autonomy of aged individuals had been valued. It is recommendable that the subject of the study could take part in new inquiries because population aging is a reality tending to expansion. The increment of studies in this area is needed; therefore the education in health is relevant for the process of human aging with quality.